Visualization of the Croatian WordNet - Katunar, Daniela (Array, 2012)
In this paper we present a visualization tool for the Croatian WordNet. We discuss two main ways of representing the Croatian WordNet – the textual and tree structure view. We point out the advantages and disadvantages of the two views as well as offer a new way of interpreting the visualization representation in terms of radial structures, a third way of representing WordNet. We also discuss the types of relations the radial view incorporates, with special attention given to polysemy as an underrepresented relation in terms of WordNet visualization. Future work is discussed to include the visualization tool as the main resource in editing and enriching the Croatian WordNet.